Black Cat. Vol. 06, The price of happiness - Yabuki, Kentaro (Viz Media, 2007)
Durham Glaster vows to claim the title of the "ultimate gunman" from the Black Cat and beats out of Train's friends where to find him. When the two finally meet, how far will Train go for revenge?